(untitled) (International Journal of Business, Economics and Management, 2018)
This study examined the relationship between employee loyalty and organizational citizenship behaviour in the Port Harcourt Area Command of the Nigeria Police Force. The study adopted a cross-sectional survey research design. The primary source of data was a structured self-administered questionnaire. The population of this study consists of Senior Police officers from the rank of Assistant Superintendent of Police (ASP) and above, and the other ranks made up of Inspectors and Non-Commissioned Officers (NCOs) working in the twenty-seven (27) Police Divisions distributed in four (4) Local Government Areas of Rivers State, Nigeria which has a total staff strength of 14,886. Due to the large size of the population, the Taro Yamane Sample Size determination techniques were used to determine the sample size of 390 employees, which were selected through stratified random sampling. Internal reliability of the instrument was achieved through the Cronbach Alpha coefficient with items being above 0.70. After data cleaning, only data of 332 respondents were finally used for data analysis. The Pearson’s Product Moment Correlation tool was used for hypothesis testing. The study findings revealed that there is a positive significant relationship between employee loyalty and organizational citizenship behaviour. The study thus concluded that employee loyalty bears a positive and significant influence on organizational citizenship. Managers should endeavour to develop a supportive connection with employees in a manner that would enhance employees desire to act or perform beyond their required role.